Kontribusi Filsafat Pendidikan Kritis Terhadap Pendidikan Demokrasi di Indonesia - Egiana Br. Sitepu; Usman AlHudawi (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Critical philosophy of education plays an essential role in shaping students' critical thinking and influencing the teaching approach of democracy and citizenship education in Indonesia. Critical education focuses on the students’ ability to think reflectively and responsibly, understanding the relationship between knowledge, power, and freedom in a democratic society. This paper examines the contribution of critical philosophy of education to democratic education through a case study in several Indonesian schools that implement a critical approach in civic education. The aim of the research is to understand the implementation of critical education philosophy in teaching democracy and citizenship, and to see how it affects students' abilities to actively participate in the democratic process. The findings suggest that the application of critical philosophy of education can raise students' awareness of social and political issues and encourage them to be more active in community activities, though significant challenges remain in achieving consistent implementation.